The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4dt01524j
|View full text |Cite
|
Sign up to set email alerts
|

Structure and photoluminescence properties of a rare-earth free red-emitting Mn2+-activated KMgBO3

Abstract: In this combined X-ray diffraction and photoluminescence study, the coordination environment of Mn(2+) and the photoluminescence of single Mn(2+) doped KMgBO3 phosphors were studied. Mn(2+) occupies Mg(2+) sites, which were coordinated by six O(2-). The strong absorption of KMgBO3:Mn(2+) was ascribed to the strong relaxation of spin and parity forbidden d-d transitions of Mn(2+). The emission bands were centered at 636 nm, regardless of the excitation wavelength and Mn(2+) doping concentration. Mn(2+) activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 31 publications
(31 reference statements)
0
28
0
Order By: Relevance
“…Eu 2+ (60 nm), 20 KMgBO 3 :Mn 2+ (70 nm). 21 It can be observed that the emission band is asymmetric. This phenomenon is caused mainly by efficient energy transfer from the defectrelated emission.…”
Section: Resultsmentioning
confidence: 99%
“…Eu 2+ (60 nm), 20 KMgBO 3 :Mn 2+ (70 nm). 21 It can be observed that the emission band is asymmetric. This phenomenon is caused mainly by efficient energy transfer from the defectrelated emission.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 In order to prove the Eu 3+ ions occupy Zn 2+ sites in Ba 2 ZnB 2 O 6 : Eu 3+ , the renement of the XRD patterns of Ba 2 ZnB 2 O 6 :Eu 3+ by Rietveld method 20,21 within the Fullprof Program 22 were performed. Renement of the structure parameters from diffraction data can obtain the crystal structure properties, such as the lattice parameters, the atomic positions of the doped ions, and occupancies.…”
Section: Resultsmentioning
confidence: 99%
“…Renement of the structure parameters from diffraction data can obtain the crystal structure properties, such as the lattice parameters, the atomic positions of the doped ions, and occupancies. 18,19 In order to prove the Eu 3+ ions occupy Zn 2+ sites in Ba 2 ZnB 2 O 6 : Eu 3+ , the renement of the XRD patterns of Ba 2 ZnB 2 O 6 :Eu 3+ by Rietveld method 20,21 within the Fullprof Program 22 were performed. It is found that the Ba 2+ sites cannot be occupied because of the nal agreement factors are very high and the occupancy of Eu 3+ on this site is far away from the nominal doping content.…”
Section: Resultsmentioning
confidence: 99%
“…31 The decay lifetimes of the three decay curves all gradually decrease with increasing dopant contents because of the rising possibility of exchange interaction between Mn 2+ ions. 32 The difference in the lifetimes of different decay curves comes from the different energy transition rate of different luminescent centers. 33 In addition, the concentration-dependent PL spectra are evaluated in Fig.…”
Section: Photoluminescent Properties Of Lzpm Xmentioning
confidence: 99%
“…S2 (ESI †), in which the intensity increases with the dopants until reaching a maximum at x = 0.14 and then decreases due to the exchange interaction between Mn 2+ ions. 32 To verify the valence state of Mn ions in the doped samples, K-edge X-ray absorption near edge structure (XANES) is usually regarded as a powerful tool, from which the Mn edge and preedge absorption peak of LZPM 0.14 are more coincident with those of MnO rather than MnO 2 (Fig. 2b).…”
Section: Photoluminescent Properties Of Lzpm Xmentioning
confidence: 99%